(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Unilateral spatial neglect is likely to be associated with poor functional outcome in sub acute phase. During this period, intensive rehabilitation is needed to obtain higher ADL scores. If greater efficacy of rehabilitation can be brought about by early intervention for unilateral spatial neglect, patients with unilateral neglect might achieve higher ADL goals. Material and Method: In this pre-post intervention study 25 neglect patients were included with less than six month of stroke.Tactile stimulations and joint integrity exercise protocol was set for four weeks. After pre-post assessment, data was analysed with help of appropriate statistical methods. Results: According to this study, there is increase in tactile stimulation (p=0.0023), kinaesthetic stimulation (p<0.0001),stereognosis (p<0.0001) and motor outcome (p=0.0001). This indicates an overall increase in sensory and motor outcome. Conclusion: Tactile stimulation and joint integrity exercises appears to be beneficial for improving motor outcome in hemineglect patients after stroke.